128k views
2 votes
The general form of an parabola is 2x2−12x−3y+12=0 .

What is the standard form of the parabola?

User Cbender
by
4.8k points

2 Answers

4 votes

Answer:

I took the test

Explanation:

The general form of an parabola is 2x2−12x−3y+12=0 . What is the standard form of-example-1
User Ranish
by
5.1k points
0 votes

Answer:

The standard form of the parabola is
(x-3)^2=4*(3)/(8)(y+2)

Explanation:

The standard form of a parabola is


(x-h)^2=4p(y-k).

In order to convert
2x^2-12x-3y+12=0 into the standard form, we first separate the variables:


2x^2-12x+3y+12=0\\\\2x^2-12x+12=3y

we now divided both sides by 2 to remove the coefficient from
2x^2 and get:


x^2-6x+6=(3)/(2)y.

We complete the square on the left side by adding 3 to both sides:


x^2-6x+6+3=(3)/(2)y+3


x^2-6x+9=(3)/(2)y+3


(x-3)^2=(3)/(2)y+3

now we bring the right side into the form
4p(y-k) by first multiplying the equation by
(2)/(3):


(2)/(3) *(x-3)^2=(2)/(3) *((3)/(2)y+3)\\\\(2)/(3) *(x-3)^2=y+2

and then we multiplying both sides by
(3)/(2) to get


(x-3)^2=(3)/(2) (y+2).

Here we see that


4p=(3)/(2)


\therefore p=(3)/(8)

Thus, finally we have the equation of the parabola in the standard form:


\boxed{(x-3)^2=4*(3)/(8)(y+2)}

User PixelsTech
by
4.9k points